Performance for Ajay - Yazdanpanah, Reza; Stewart, Jesse (Critical Studies in Improvisation / Études critiques en improvisation, 2025)
Reza Yazdanpanah and Jesse Stewart perform an improvised tar and drum kit collaboration.